Cosmolocalism Against Platform Capitalism: Evidence From Ridesharing - Yosuke Uchiyama (tripleC: Communication, Capitalism & Critique)
The rise of digital commons has expanded shared resources and addressed some challenges of traditional commons. However, this expansion has created new boundaries, forming a complex paradigm that challenges platform capitalism and demands alternative governance models. This study conceptualises shared resources within the framework of cosmolocalism, examining their formation, the processes of enclosure under platform capitalism, and potential pathways for de-embedding. Platform capitalism utilises legal frameworks and opaque algo-rithmic systems to appropriate resources and dominates digital labour markets, manifesting a contemporary tragedy of the commons characterised by exploitation and profit maximisation. Using ridesharing as a case study, this research highlights the dynamic nature of cosmolocal-ism and proposes strategies to counter exploitation. By integrating platform cooperativism and social common capital, this study offers sustainable, equitable resource management solu-tions, supported by a comparative analysis of business models.